Effect of the long-term application of anaerobically digested residual slurry on methane emissions in a rice paddy field. Issue 3 (4th May 2017) - Tanaka, Takashi S. T.; Nitta, Yoshiro; Kido, Kaoru; Nishikawa, Tomohiro; Matoh, Toru; Inamura, Tatsuya
ABSTRACT: The anaerobic digestion of livestock manure is an environmentally compatible technology used for the production of renewable energy. Anaerobically digested residual slurry has been used worldwide as a liquid fertilizer in both upland and paddy fields. However, a controversial question remains as to whether the application of slurry to rice paddy fields increases methane emissions; although methane is one of the most prevalent greenhouse gases, little is known about the effects of the long-term application of residual slurry on methane emission. In this study, we repeatedly applied slurry to a paddy field for six years at different application rates (10, 15, and 20 g N m −2 based on ammonium-nitrogen content). At the fifth and sixth years of application, we evaluated the effect in terms of methane flux and soil total carbon content. The effect of the long-term application of the slurry (10 g N m −2 ) on grain yield was equivalent to that of chemical fertilizer (10 g N m −2 ). The application of the residual slurry was likely to increase the cumulative methane emissions during rice growing season in both 2006 and 2007. On the other hand, we observed that soil total carbon did not accumulate significantly in the soil. Thus, we cannot rule out the potential risk of additional methane emissions caused by the application of the residuary slurry to paddy fields.